2008
DOI: 10.1007/s10750-008-9443-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of variable nutrient additions on a pond mesocosm community

Abstract: The effects of nutrient additions on aquatic systems have been frequently studied. Typically, these studies report an increase in algal biomass and a decrease in species diversity in response to nutrient increases. However, it is not clear why comparable aquatic communities respond differently to nutrient additions of similar magnitudes. We tested the effects of the rate and amount of nutrient load on community structure in 760 l mesocosms; treatments manipulated the total amount of nutrients that entered an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…As proposed for terrestrial ecosystems, their "carrying capacity" may not yet have been reached (MASSÉ et al, 2001). The short-lived disturbances associated with the seasonal passage of the birds are likely too transitory to perturb the systems outside their range of natural variability (BUTZLER and CHASE, 2009). This suggests that the Greater Snow Goose population will likely not profoundly alter the water quality in Sirmilik National Park unless a continuously growing population is kept in proximity to a single site for an extended period of time, which is a likely scenario according to the ACIA (2004) report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As proposed for terrestrial ecosystems, their "carrying capacity" may not yet have been reached (MASSÉ et al, 2001). The short-lived disturbances associated with the seasonal passage of the birds are likely too transitory to perturb the systems outside their range of natural variability (BUTZLER and CHASE, 2009). This suggests that the Greater Snow Goose population will likely not profoundly alter the water quality in Sirmilik National Park unless a continuously growing population is kept in proximity to a single site for an extended period of time, which is a likely scenario according to the ACIA (2004) report.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested that in high latitude lakes, increased nutrient levels do not necessarily influence phytoplankton due to low water temperatures (FLANAGAN et al, 2003), low photosynthetic rates (MARKAGER et al, 1999) and intense grazing by zooplankton in "two-level" food webs (HANSON et al, 1992;VAN GEEST et al, 2007). It has also been suggested that the loading rate is at least as important as the total amount of nutrients added to the system (BUTZLER and CHASE, 2009). A single pulse of nutrient may result in nutrients remaining in the water column for a short period of time before being incorporated into the sediments.…”
Section: Biotic Variables (Chlorophyll-a)mentioning
confidence: 99%
“…A better approach would be to focus on predicting temporal variation in the nutrient concentrations observed from grab samples. Models that could predict both spatial and temporal variation would provide a better basis for establishing criteria and could provide potentially important ecological information on the location and timing of natural nutrient fluctuations that influence primary producers (e.g., Butzler and Chase 2009).…”
Section: Model Shortcomings and Possible Improvementsmentioning
confidence: 99%